PENERAPAN EVIDENCE BASED NURSING TERAPI RELAKSASI BENSON PADA PASIEN DENGAN NYERI POST SECTIO CAESAREA DI RS BHAYANGKARA TK.I R SAID SUKANTO - Tiara Fadjriyaty (2022)
Sectio caesarea is a surgical procedure that is carried out to assist the mother in removing the fetus by performing injuries such as making an incision in the abdominal area and the mother's abdominal wall. Sectio caesarea action resulted in the disruption of tissue continuity and the presence of wounds in the mother's abdominal area so that it would cause the mother to feel pain in the wound area. The pain experienced by the mother can be overcome in two ways, namely pharmacological and non-pharmacological therapy. There are many ways that can be done to treat pain non-pharmacologically, one of which is Benson relaxation therapy. Beson relaxation therapy is an act of combining relaxation techniques and beliefs that the patient has in dealing with pain. When this therapy is carried out the body will release endorphins which have a function to restrain the transfer of pain impulses in the central nervous system so that pain is reduced. The measurement instrument used to measure the pain scale in post sectio caesarea mothers is the Numeric Rating Scale (NRS). The results of the implementation after Benson relaxation therapy 1-2 times a day with a time of 10-20 minutes showed a decrease in the pain scale in post sectio caesarea patients. Therefore, mothers with post-section caesarea are advised to use Benson's relaxation therapy as a non-pharmacological therapy to reduce pain scale.